KINERJA LEMBAGA PENJAMINAN MUTU PENDIDIKAN (LPMP) DALAM PENJAMINAN MUTU SEKOLAH DASAR:Studi Kasus Pada LPMP Provinsi Jambi - Rosadi, Kemas Rosadi (2012)
Problems of this study is based on the fact that performance in quality assurance of education LPMP the Optimal Primary School yet. It is apparent from the graduation rate at primary school level is still low. Efforts made to overcome these problems is to apply the management functions Deming refers to the model.This study aims to describe and analyze the quality assurance of education in primary schools, to maximize the application of management functions include: planning, implementation, monitoring and review. The approach used in this study is a qualitative method. The technique used to collect data was observation, interviews and documentation studies. Analysis of the data used is the reduction of data, display data, conclusions and verification, and technical data validity checks. Conclusion The study showed that: Planning undertaken by LPMP on primary education was formulated referring to the vision, mission and goals, then made an annual work program, medium and long outreach. Planning program created LPMP not optimal and not involve all stakeholders of education. Implementation of program activities during the years 2009-2011 LPMP on PMS implementing section 54 activities, carrying out 27 activities PSI section, section 97 FSDP implement activities. Of the planned activities are still many that have not been implemented. Discrepancy was found between the plans are made with the implementation of program activities on the ground. Monitoring conducted by quality assurance LPMP in primary schools found that some activities are not implemented at this stage of planning or preparation. Review of related LPMP produce output in the form of education quality assurance services. Review this section refers to optimizing the performance of PMS, PSI and the FSDP. In conducting the review LPMP do not look good preparation this can be seen from the officers who have not worked as expected format provided. In general it can be concluded that the performance is not optimal because LPMP a task that was not his job like TRAINING and WORKSHOP see the Minister of National Education Regulation number: 07. 2007. Suggestions: Performance LPMP future should focus on developing quality assurance of education is not just a routine course of training and workshops. LPMP must be responsive to issues and problems of education in the province of Jambi and at follow-up with local government and related agencies.